1998
DOI: 10.1007/s005350050149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pirenzepine on gastric endocrine cell kinetics during lansoprazole administration

Abstract: We studied the effect of pirenzepine on gastric secretion kinetics in rats in a hypochlorhydric state induced by lansoprazole, a proton pump inhibitor. Pirenzepine was administered intramuscularly at a dosage of 20 mg/kg twice daily; and lansorprazole, subcutaneously at 50 mg/kg once daily, both every day for 4 weeks. After the 4-week treatment, serum gastrin and plasma somatostatin levels were determined by radioimmunoassay. In addition, gastrin cells, somatostatin cells, and enterochromaffin-like cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This enlargement is due to parietal cell hypertrophy and is accompanied by hyperplasia. These changes are thought to be due to PPIinduced hypergastrinemia, and studies have shown that the antrum can show increased numbers of gastrin-secreting G cells [15,16]. On a practical level, hypertrophy and hyperplasia are noted by the presence of parietal cell extension up to the level of the foveolar neck region, as well as enlarged, crowded parietal cells with luminal bulging within deeper glands (parietal cell protrusions), and are highly suggestive of PPI use (Fig.…”
Section: Parietal Cell Changes 231 Proton Pump Inhibitorsmentioning
confidence: 95%
“…This enlargement is due to parietal cell hypertrophy and is accompanied by hyperplasia. These changes are thought to be due to PPIinduced hypergastrinemia, and studies have shown that the antrum can show increased numbers of gastrin-secreting G cells [15,16]. On a practical level, hypertrophy and hyperplasia are noted by the presence of parietal cell extension up to the level of the foveolar neck region, as well as enlarged, crowded parietal cells with luminal bulging within deeper glands (parietal cell protrusions), and are highly suggestive of PPI use (Fig.…”
Section: Parietal Cell Changes 231 Proton Pump Inhibitorsmentioning
confidence: 95%
“… 14 In animal experiments, hypergastrinaemia, even if induced by exogenous administration of gastrin or caused by proton pump inhibitor‐induced inhibition of gastric acid secretion, had a potent selective trophic effect on gastric ECL cells. 15–17 These clinical and experimental data suggest that gastrin directly stimulates only the proliferation of ECL cells in the gastric mucosa.…”
Section: Gastrin‐induced Stimulation Of Gastric Mucosal Proliferationmentioning
confidence: 98%
“…The finding of Tari et al 9 suggests that somatostatin, which is secreted by fundic D cells, may be involved in the mechanism by which pirenzepine inhibits the omeprazole-induced histamine secretion and synthesis in ECL cells. Omura et al 11 have shown that pirenzepine suppresses the increase in the number of ECL cells induced by lansoprazole in the rat. Pirenzepine may suppress not only histamine secretion and synthesis but may also inhibit the proliferation of ECL that is induced by a proton pump inhibitor.…”
mentioning
confidence: 99%